The Effect Of Return On Assets And Inflation On Stock Prices In The Banking Sub-Sector On The Indonesian Stock Exchange In 2017 – 2022 - Nabilah Fary Adiyana; Egi Gumala Sari (Yayasan Az Zukhruf Cendikia, 2024)
Purpose – This study aims to examine the impact of Return on Asset (ROA) and inflation on stock prices in the banking sub-sector companies listed on the Indonesia Stock Exchange from 2017 to 2022. Design/methodology/approach – The study employs a quantitative research method. A sample of 25 banking companies listed on the Indonesia Stock Exchange was selected. The analysis was conducted using multiple regression techniques, and the data was analyzed using Eviews9 software to test the hypotheses. Findings – The findings reveal that both Return on Asset and inflation variables have a positive, but statistically insignificant, effect on stock prices. Research limitations/implications – This study is limited to banking sub-sector companies listed on the Indonesia Stock Exchange during the 2017-2022 period, which may limit the generalizability of the findings. Future research could expand the sample to other sectors or time periods to gain more comprehensive insights. The results provide useful information for decision-makers and can serve as reference material for future research.